Capturing language disparity: Considerations for theory and practice - Éluère, Manon; Pougué Biyong, Clémence (Management international / International Management / Gestiòn Internacional, 2022)
Language is a quantifiable and valuable resource to possess. It can also represent a source of inequality within a group, where some team members would have access to information and be able to engage in social interactions whereas others would not. This methodological and empirical study aims at introducing a new index – the Matiti index – to capture language disparity in an accurate and practical way. An illustration of how this index can be operationalized to inform research is provided by relying on a unique database collected during an empirical study gathering 21 high-level women football teams. This article highlights both methodological and practical implications.